Targeted therapy of acute myeloid leukemia. Issue 4 (April 2015) - Carneiro, Benedito A; Altman, Jessica K; Kaplan, Jason B; Ossenkoppele, Gert; Swords, Ronan; Platanias, Leonidas C; Giles, Francis J
Abstract : Advances in the understanding of the genetic underpinnings of acute myeloid leukemia are rapidly being translated into novel treatment strategies. Genomic profiling has highlighted the importance of the epigenetic machinery for leukemogenesis by identifying recurrent somatic mutations involving chromatin-modifier proteins. These genetic alterations function as dynamic regulators of gene expression and involve DNA-methyltransferase 3A, methyltransferase DOT1L, enhancer of zeste homologue 2, isocitrate dehydrogenases 1 and 2 and bromodomain-containing proteins. New therapeutic targets are also emerging from further delineation of cell signaling networks in acute myeloid leukemia blasts mediated by PIM kinases, polo-like kinase 1, cell surface protein CD98 and nucleocytoplasmic shuttling receptors, among others. Early results of targeted therapies directed at these molecular mechanisms are discussed in this review and their potential to improve the outcomes of patients by allowing the use of more effective and less toxic treatments.